1961
DOI: 10.1136/jcp.14.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Sodium, potassium, water, and haemoglobin in the packed red cells of severe thalassaemia

Abstract: SYNOPSIS Sodium, potassium, water, and the mean corpuscular haemoglobin concentration were determined in the packed erythrocytes of children with severe thalassaemia. The concentration of sodium in the packed red cells was higher than normal in a significant proportion of children with thalassaemia whereas potassium in the packed cells and sodium and potassium in the plasma were normal.On average, the cell water content was a little higher and the mean corpuscular haemoglobin concentration a little lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
1

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…This is probably due to wide variations in instrument blank values that were encountered occasionally with the Coleman nitrogen analyzer in our early studies. In this respect our experience has been similar to that of Flokstra and Nodolski (38 21 3,358 93 3,512 14 3,371 21 3,729 22 3,500 35 3,401 12 3,752 20 3,627 47 3,349 30 3 Solomon (11) and Selwyn and Dacie (9), but it is 13% higher than the results obtained by Czaczkes and co-workers (13), 6% lower than the mean value found by McCance and Widdowson, and 18% less than the value given by Choremis and associates (12) in children (Table VI). The discrepancy in results is probably due to minor differences in the composition of standards, in excitation conditions, or in the instruments used in the analysis.…”
Section: Selection Of Control Subjectssupporting
confidence: 69%
See 1 more Smart Citation
“…This is probably due to wide variations in instrument blank values that were encountered occasionally with the Coleman nitrogen analyzer in our early studies. In this respect our experience has been similar to that of Flokstra and Nodolski (38 21 3,358 93 3,512 14 3,371 21 3,729 22 3,500 35 3,401 12 3,752 20 3,627 47 3,349 30 3 Solomon (11) and Selwyn and Dacie (9), but it is 13% higher than the results obtained by Czaczkes and co-workers (13), 6% lower than the mean value found by McCance and Widdowson, and 18% less than the value given by Choremis and associates (12) in children (Table VI). The discrepancy in results is probably due to minor differences in the composition of standards, in excitation conditions, or in the instruments used in the analysis.…”
Section: Selection Of Control Subjectssupporting
confidence: 69%
“…The average sodium concentration in centrifuged erythrocytes has been reported to be from as low as 168 MAg per g (4) to as high as 443 ug per g (5), and several textbooks (6)(7)(8) give a value of approximately 400 ug per g, which is not in accord with the results of recent investigation (9)(10)(11)(12)(13). In a few studies (9-13) correction for sodium in trapped plasma has been taken into consideration, but in others (14)(15)(16)(17)(18)(19)(20)(21) it has been neglected.…”
contrasting
confidence: 53%
“…These include hyperthyroidism [21], severe cardiac failure [19], sick cell syndrome [17], metabolic alkalosis [22], thalassaemia [23], and Na depletion. Czaczkes et al [19] found RBC-Na to be low in uraemia, but Welt et al [24] described a group of patients with very high RBC-Na levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kates, Allison and James (1961) have reported an abnormal ratio of phosphatidyl ethanolamine to lysophosphatidyl ethanolamine in red cells from two patients with hereditary spherocytosis. De Gier, van Deenen, Geerdink, Punt and Verloop (1961), however, failed to confirm this.…”
mentioning
confidence: 92%
“…The increase in cell Na' was confirmed by Houtsmdler (1959), who found also an increase in red cell K+. Choremis, Nicolopoulos, Metaxotou and Moschos (1965) described a decreased cholinesterase activity in the red cells of thalassaemics.…”
mentioning
confidence: 99%